A New Data Processing Method for High-Precision Mining Subsidence Measurement Using Airborne LiDAR - Dong, Yue; Wang, Dong; Liu, Fengying; Wang, Junjie (Frontiers in Earth Science, 2022)
Coal resources are the principal energy in China, and the surface subsidence caused by coal mining has a serious impact on the safe production and life of human beings. The traditional observation method of rock movement is slow and laborious, while the accuracy of airborne Lidar, InSAR and other methods is relatively low. In this paper, aiming at the problem of low accuracy of deformation monitoring of unmanned airborne Lidar, the data registration of Lidar point cloud is analyzed by combining theoretical analysis with field experiment. An advanced distribution mode of control points is discussed, and a current method of multi-period point cloud registration using seven-parameter transformation is proposed to obtain a surface subsidence model for high precision mining area. The results show that the RMSE of airborne Lidar is improved from 0.012m to 0.0035m by using the new data registration method, and the maximum error value is reduced from 0.02m to 0.006m, which effectively enhances the deformation monitoring capability of airborne Lidar.